La successione tardo triassica del Gebel di Garian (Libia) : esemplificazione del principio di Walther - Assereto, Riccardo (Rivista italiana di paleontologia e stratigrafia, 1970)
Keywords: Géologie – Djebel Nefousa

Geology of the Garian map-area, Tripolitania and logs of the wells drilled by latas in Tripolitania between march 1953 and march 1954 - Christie, Archibald M. (United Nations mission in Libya, 1954)
Keywords: Géologie – Djebel Nefousa

Sur la découverte du Trias au pied du Djebel Garian - Brichant, André-L. (Comptes rendus hebdomadaires des séances de l'Académie des sciences, 1952)
Keywords: Géologie – Djebel Nefousa

Middle, Upper Jurassic and Lower Cretaceous sedimentary environments of the Djebel Nefusa region, northwestern Libya - Hodgkinson, Richard J.; Walley, Christopher D. (Annual report - Society for Libyan Studies, 1977)
Carbonate and clastic sediments of Jurassic and Cretaceous age are exposed along the fault-scarp of Djebel Nefusa in north-western Libya. Previous geological investigations have been mainly restricted to the eastern sector of the scarp. Recent studies by the authors in the western sector of Djebel Nefusa and on equivalent sediments in southern Tunisia have allowed the first regional interpretation of these rocks. The area studied lies geographically and geologically at the edge of the Saharan Platform, a large cratonic block, composed of rocks of Precambrian-Palaeozoic age. To the north and east lies a downfaulted sedimentary basin (Gabes-Sabratha Basin) containing a large thickness of Mesozoic sediments. The location of the sections measured along Djebel Nefusa are depicted in Fig.1. The stratigraphic nomenclature of the rock succession of Djebel Nefusa was first established in the east and continued laterally towards the west by later workers. Difficulties in the application of this nomenclature are presented by the recognition of facies changes previously overlooked by earlier investigators. However, as a framework for understanding these changes and the sedimentary processes which caused them, the stratigraphy erected by Magnier (1963) is adopted.
Keywords: Géologie – Djebel Nefousa

Examen sommaire d'une collection de roches provenant de la Tripolitaine - Meunier, Stanislas (Bulletin de la Société Géologique de France, 1905)
Keywords: Géologie – Djebel Nefousa

Geophysical Studies of North African Cenozoic Volcanic Areas: III. Garian, Libya - Ade-Hall, J. M.; Gerstein, Susann; Gerstein, Robert E.; Reynolds, Peter H.; Dagley, P.; Mussett, A. E.; Hubbard, T. P. (Canadian Journal of Earth Sciences, 1975)
Paleomagnetic and K/Ar whole rock absolute age data are described for material from the Garian area of Libya, centered at 13°E, 32°N. Within-unit cleaned paleomagnetic directions from the essentially unaltered lavas are very well defined and can almost certainly be taken as reliable measurements of the geomagnetic field direction during the initial cooling of each flow. However, the distributions of mean direction, from which the effect of repeated sampling of the field at one time has been removed, does not suggest that a reversing axial dipole field has been recorded in a representative manner. Both N and R groups of directions are azimuthally elongated, and the average poles for the N and R groups differ by 21°, or four times the 95% level uncertainty for each average pole. A number of possible physical explanations for the paleomagnetic results are discussed. The conventional overall average pole at 88°N, 123°E, δp: 3°, δm: 7 °does not differ significantly from the geographic pole, a result which agrees closely with that of Schult and Soffel (1973). However, the value of these overall average poles in estimating absolute plate motion must await an understanding of the sources of the asymmetries in the paleomagnetic data.
Keywords: Géologie – Djebel Nefousa

Formazioni basaltiche del Gebel Nefusa (Tripolitania) - Taronna, Giorgio (Universita degli Studi di Padova, 1961)
Keywords: Géologie – Djebel Nefousa

Lithic Raw Materials of the Late Palaeolithic/Neolithic Industries in Jabal Nefusa, Tripolitania - Mrazek, Ivan; Svoboda, JIŘÍ (Anthropologie, 1986)
The mineralogic-petrographical character of the raw materials of the Late Palaeolithic/Neolithic stone industries, collected at several open air-sites in the area of Jabal Nefusa, have been studied and the origin of the raw materials have been recognized. Two types of Upper Cretaceous (Nalut Formation) cherts (the coloured and the striped ones), used for the manufacture of implements, have been distinguished. They may be considered either local or short-distance imported raw materials.
Keywords: Géologie – Djebel Nefousa

Large-scale landslides in north-western Libya - Ostaficzuk, Stanislaw (Acta Geologica Polonica, 1973)
Keywords: Géologie – Djebel Nefousa

The Umm et-Grib rock-shelter and the exploitation of resources in Jebel Gharbi - Conati Barbaro, Cecilia (Libya Antiqua, 1995)
Keywords: Géologie – Djebel Nefousa

Stratigraphic studies on Quaternary floodplain deposits of the Eastern Gefara Plain. S.P.L.A.J. - Anketell, J. M.; Ghellali, S. M. (Libyan Studies, 1983)
Abstract The Quaternary deposits of the Gefara Plain are comprised of three major facies – alluvial fan facies of sands and gravels which blankets the base of the Jebel Nafusa escarpment; floodplain facies of fluvial sands and silts with aeolian dunes which underlies most of the Gefara Plain and, aeolian coastal dune facies, predominantly calcarenitic, which is confined to a narrow coastal zone. Well exposed sections in the eastern part of the plain allow sub-division of the floodplain deposits into a number of mappable units defined and bounded by surfaces of stratigraphic discontinuity. The lithologies of these units are described and compared from selected type sections. The relationships between the units, their geometry, and the nature of the surfaces of stratigraphic discontinuity are discussed. It is proposed that, the lithostratigraphic sequence displayed by the Quaternary floodplain deposits of the eastern Gefara region provides a firm basis for correlation, not only with floodplain deposits in other parts of the plain but also with the other major facies developed in the area. In addition, the recognition of significant stratigraphic breaks in the sedimentary sequence combined with facies analysis lays a firm foundation for an interpretation of the geological history of the region.
Keywords: Géologie – Djebel Nefousa

Quaternary Deposits of Northern Libya — Lithostratigraphy and Correlation - Anketell, J. M. (Libyan Studies, 1989)
In recent years basic regional geological mapping of northern Libya by the Industrial Research Centre, Tripoli, together with the UNESCO Libyan Valleys Survey of eastern Tripolitania and the work of the author and Dr S. M. Ghellali in the Jifarah Plain and Jabal Nafusah, have greatly added to our knowledge of Quaternary deposits in the region. This work is described and evaluated against the background of earlier studies. The succession of major depositional, soil forming and erosional events which characterise the fluvio-aeolian deposits of the Jifarah Formation can be recognised in, and thus used to subdivide, laterally equivalent aeolianite, fangravel and wadi gravel deposits in the Jifarah Plain. Comparisons of this succession with others from throughout the region indicate that the events are of regional significance and that the Jifarah sequence provides a sound framework for lithostratigraphic correlation and a basis for facies analysis and chronostratigraphic studies. This review is largely limited to the northern margins of Libya north of the 30th parallel (Fig. 1). It is convenient to subdivide the zone into several regions. These are: (a) The Jifarah Plain and foothills of the Jabal Nafusah. (b) The Hammada Al Hamra Plateau and major valleys of eastern Tripolitania. (c) The coastal region from Misratah to Ajdabiyah. (d) Cyrenaica from Soluq to Al Bardia.
Keywords: Géologie – Djebel Nefousa

The significance of the occurrence of Abu Ghaylan and Kiklah Formations east of Wadi Ghan, eastern Jabal Nfusah - Fatmi, A. N.; Sbeta, Ali (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie – Djebel Nefousa

Depositional environments of the Chicla, Cabao and Chameau Mort Formations as revealed by scanning electron microcopy - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Water resources of the Socialist People's Libyan Arab Jamahiriya - Pallas, D. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Structural control of groundwater flow in the Mesozoic sandstone aquifers of the eastern part of Jabal Nafusah, Libya. - Singh, G. D. S. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Stratigraphy and lithofacies of the continental clastics (Upper Jurassic and Lower Cretaceous) of Jabal Nafusah, NW Libya. - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Stratigraphic nomenclature of the pre-Upper Cretaceous Mesozoic rocks of Jabal Nafusah, NW Libya. - Fatmi, A. N.; Eliagoubi, B. A.; Hammuda, O. S. (The geology of Libya. Volume I. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978., 1980)
Keywords: Géologie – Djebel Nefousa

Some geochemical aspects of Al Aziziyah Formation, Jabal Nafusah - Ben Ashour, A. M.; Zaied, A.; Bakush, M. (The geology of Libya. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Keywords: Géologie – Djebel Nefousa

The geology of Libya: Third Symposium on the Geology of Libya - Salem, M. J.; Hammuda, O. S. (Elsevier, 1991)
Meeting Name: Symposium on the Geology of Libya
Keywords: Géologie – Djebel Nefousa

Geochemical position of the Jabal Nafusah phonolites - Bausch, W. M.; Meduna, J. U. (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie – Djebel Nefousa

Mineralogical composition of Jabal Nafusah phonolites - Bausch, W. M. (Academic Press, 1980)
The Jabal Nafusah phonolites are characterized by the dominance of felsic components, or a very low colour ratio. As mentioned by Almond et al. (1974), phenocrysts (mostly of alkali feldspar) may occur, but generally the phonolites are fine grained, poorly crystallized or even aphyric. Along with microscope analysis, the mineralogical composition has been investigated, essentially by means of X-ray diffraction. The chief (felsic) components found were: sanidine, analcime, nepheline, sodalite and albite (given in order of approximately decreasing frequency). The frequency of analcime is quite remarkable, and has not been hitherto described. Also shown are the relations of changing proportions of mineralogical compositions and detailed X-ray data.
Keywords: Géologie – Djebel Nefousa

Geomorphology and sedimentology in the Ghan and Zargha Wadis and on the Jado Plateau - Giraudi, Carlo (Libya Antiqua, 1995)
Keywords: Géologie – Djebel Nefousa

Remarques sur la stratigraphie du Jebel Nefusa - Burollet, Pierre-Félix (Rivista Italiana di Paleontologia e Stratigrafia, 1966)
Keywords: Géologie – Djebel Nefousa

Evaporite, carbonate, and siliciclastic transitions in the Jurassic sequences of southeastern Tunisia - Ben Ismail, Mohamed Hédi; M'Rabet, Ali (Sedimentary Geology, 1990)
Evaporite, carbonate and siliciclastic transitions occur within the Jurassic deposits of southeastern Tunisia. These facies are grouped into four major transgressive-regressive sequences corresponding to various environments of deposition. The latter include sabkha, subaqueous evaporite basin, carbonate tidal flats to shallow marine platform, bioherms and mixed siliciclastic ramp. Rapid lateral and vertical variations in thicknesses and facies are controlled by tectonic, climatic and eustatic factors. East-west and NW-SE fault systems generated a down-faulted graben (Tataouine basin) bordered by two uplifted horsts (Tebaga Mole and Libyan Craton) and have acted as an evaporite depocenter or as a siliciclastic trap. Eustatic-related transgressions occurring during Late Lias, Bajocian, Early/Middle Callovian, and probable Upper Callovian-Oxfordian have led to opening and/or deepening of the marine basin accompanied by carbonate sedimentation rapidly replacing evaporite or siliciclastic deposition. This Jurassic example not only confirms that tectonics and, to a lesser extent, climate largely controlled evaporite, carbonate, and siliciclastic transitions; it also demonstrates that sea-level changes may be another factor controlling such transitions in these ancient deposits.
Keywords: Géologie – Djebel Nefousa